Analisis Kemampuan Cacing Tanah (Lumbricus rubellus) Sebagai Agen Akumulator Logam Berat Timbal Selama Proses Vermikomposting Tanah Tercemar - Renaldi, Riki; Sari, Gina Lova; Ratnawati, Kania (Universitas Tanjungpura, 2025)
Contaminated soil with heavy metal lead (Pb) can be remediated using environmentally friendly biological technologies, one of which involves the use of earthworms (Lumbricus rubellus). This study aimed to evaluate the ability of Lumbricus rubellus as a bioaccumulator of lead during the vermicomposting process of contaminated soil. The vermicomposting experiment was conducted under aerobic conditions for 56 days with observations made every 14 days (on days 0, 14, 28, 42, and 56) at a laboratory scale. The study consisted of two experimental variations: Reactor A, which contained a 1:1 ratio between contaminated soil and organic vermicomposting materials (cow manure and cabbage waste), and Reactor B, with a 1:2 ratio. Each reactor was inoculated with 75 adult Lumbricus rubellus earthworms weighing approximately 0.70